Use of residual drift for post-earthquake damage assessment of RC buildings. (15th September 2017) - Dai, Kaoshan; Wang, Jianze; Li, Bowei; Hong, H.P.
Highlights: Two approaches were studied for peak drift predication based on residual drift of a building. A full-scale shaking table test was adopted as a case to assess these two methods. The probabilistic-based framework was recommended for seismic assessment of buildings. Abstract: Large earthquakes cause damage to buildings. The peak nonlinear inelastic responses of a building for given seismic ground motions are often used as a proxy for the damage measure. However, the peak responses are rarely recorded or observed for an earthquake event. The residual drift or the permanent deformation of the building after the seismic event can be measured and may be used to infer the degree of sustained damage of the building. Although the use of the residual drift to infer the seismic performance of buildings under earthquakes was explored in the literature, its validation by using full-scale experimental data is unavailable. In this study, test results of a full-scale four-story Reinforced Concrete (RC) building were used as the basis to assess the adequacy of using the residual drift to estimate the damage sustained by the building subjected to ground motions. The seismic performance assessment of this tested building was performed with the peak roof drift calculated from the residual deformation. Analysis results indicated that the approach could be used to infer probabilistically the peak drift of the building based on its residual drift. The degree of uncertainty in this inference is large and should be considered as an integral part of this estimation. Additional issues of using the residual drift as a measure of seismic performance of the building were discussed.